Rituximab and Therapeutic Plasma Exchange in Recurrent Focal Segmental Glomerulosclerosis Postkidney Transplantation - Alasfar, Sami; Matar, Dany; Montgomery, Robert A; Desai, Niraj; Lonze, Bonnie; Vujjini, Vikas; Estrella, Michelle M; Manllo Dieck, John; Khneizer, Gebran; Sever, Sanja; Reiser, Jochen; Alachkar, Nada (Transplantation, 2018)
Focal segmental glomerulosclerosis (FSGS) is a common cause of end-stage renal disease with a high rate of recurrence after kidney transplantation. Several factors, such as white race, rapid progression, and previous allograft failure due to recurrence, were found to be risks of recurrence. Data are limited on the benefits of rituximab and/or therapeutic plasma exchange (TPE) in preventing recurrence. In this study, we sought to assess the efficacy of rituximab and TPE for the prevention and treatment of recurrent FSGS after kidney transplantation. We enrolled 66 patients with FSGS in this prospective observational study and followed their outcomes. Patients with high risk for recurrence received preventative therapy with TPE and/or rituximab. Twenty-three (62%) of the 37 patients who received preventative therapy developed recurrence compared with 14 (51%) recurrences of the 27 patients who did not receive any therapy (P = 0.21). There was a trend for less relapse when rituximab was used as a therapy for recurrent FSGS (6/22 vs 9/18, P = 0.066). We used a clinical score of 5 values to assess the prediction of FSGS recurrence. A score of 3 or more had a predictive receiver operating characteristic curve of 0.72. Treatment with TPE and/or rituximab resulted in better allograft survival than historical studies. Allograft failure because of recurrent FSGS occurred in only 6 (9%) patients. Preventative therapies do not decrease the recurrence rate of recurrent FSGS. However, prompt treatment of recurrence with these therapies may result in improved outcomes.